HeartMate 3 in Lowest INTERMACS Profile Cohort: The Swiss Experience. Issue 6 (November 2017) - Tozzi, Piergiorgio; Banfi, Carlo; Ahmadov, Kameran; Hullin, Roger; Meyer, Philippe; Giraud, Raphael; Liaudet, Lucas; Gronchi, Fabrizio; Huber, Christophe; Kirsch, Matthias
Abstract : New generation devices for long-term mechanical circulatory support are centrifugal pumps having fully magnetically levitated rotors to reduce blood trauma. Recently, the novel HeartMate 3 was cleared for clinical application in Switzerland. In two Swiss University Hospitals part of the "Lausanne–Geneva Transplantation Network, " 10 consecutive patients in end-stage heart failure received the HeartMate 3 (Thoratec Corporation, Pleasanton, CA). Device implantation criteria were persistent low output syndrome despite optimal medical treatment. The primary end-point of the study was survival or transplantation to 90 days on the device. Five patients (50%) were in Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) class 1 and 2 (two were under venoarterial extracorporeal membrane oxygenation [VA-ECMO]), and five were in class 3 and 4. The indication was bridge-to-transplant in seven patients, and destination therapy in three. Two patients (20%) received concomitant aortic valve surgery. Four patients (40%) required temporary right ventricle support (tRVAD) for a mean of 8 ± 1.5 days. Bleeding requiring surgical revision occurred in five (50%) patients, two during the tRVAD support. At the 90 day end-point, survival was 90%, one (10%) died due to respiratory failure. Three (30%) experienced critical illness polyneuropathy. Two had body temperature over 38.5°C for more than 7 days after implant, without infections. Two (20%) had late driveline infection. The pump allowed rapid improvement of patients' clinical conditions even in severely compromised patients. Postoperative bleeding occurred in the setting of anticoagulation. No hemolysis or pump thrombosis occurred. Fever occurred frequently but was not associated with mortality. Hemodynamic support was consistent over time without significant adverse events. Abstract : Supplemental Digital Content is available in the text.